Five Models Used in Contrastive Semantics: A Comprehensive Synthesis and Analysis - Toan, Ly (International Journal of Language and Literary Studies, 2024)
The present study aims to assess and contrast five different approaches in the field of contrastive semantics: natural semantic metalanguage (NSM), conceptual metaphor theory (CMT), frame semantics (FC), semantic field theory (SFT), and cognitive grammar (CG). The research is set to review the available literature on the described techniques in order to focus on their distinguishing characteristics, practical applications, and illustrative samples. The findings reveal that these five models do play an insightful role when it comes to analyzing and comparing synonymous and semantically related profiles across distinct languages. Relations of semantic elements are the core concern of NSM while CMT investigates the internal schemata of the mind. As opposed to cognitive frame analysis, where knowledge structures are the central object of study, in SFT are language units grouped according to their meaning, while CG sees no separation of grammatical and meaning structures. This paper expounds on how these frameworks fill the gaps left by each of them and offers a broader understanding of the ways words encode meaning and how speakers of different cultures think about the world. Moreover, this study augments the knowledge regarding the variations of languages and gives an understanding of how languages relate to cognition, culture, and how people think about the world through words.